A Gendered Model of the Peasant Household: Time poverty and Farm Production in Rural Mozambique. Issue 2 (3rd April 2017) - Arora, Diksha; Rada, Codrina
ABSTRACT: Using insights from a case study on the allocation of labor in subsistence households in Mozambique, this study develops a conceptual framework for examining linkages between time poverty and farm production. An unexpected event such as a health crisis increases the demand for labor provided by women, thus making them more time poor. The model and numerical simulations show that a deterioration in a woman's time constraint will have an adverse effect on agricultural output of the household. This occurs because most women respond to an increase in household work by reducing their work hours on the farm and by reducing their leisure time. The latter outcome is expected to have a negative effect on women's physical and mental health, which will then cause a decline in their productivity on the farm.